Salicylic acid improves seed germination through modulating antioxidant enzymes under salt stress in chickpea (Cicer arietinum) - P, VIJAYAKUMAR H; R, DHANDAPANI; G, SOMASUNDARAM; S, NATARAJAN; RAJENDRAN, AMBIKA; K, SWARNALAKSHMI; G, JOSHY C; M, BORAIAH K (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted to investigate the role of Antioxidant Enzymes (AOE) in Salicylic Acid (SA) induced salt-stress tolerance during chickpea (Cicer arietinum L.) seed germination at ICAR- Indian Institute of Seed Science, Mau during 2018. Results showed the differential germination performance of salt-sensitive (PG 186) and salt-tolerant (CSG 8962) chickpea cultivars under three levels (0, 75, 150 mM NaCl) of salt stresses. Salt stress adversely affected the seed germination and traits of early seedling establishment in PG 186 cultivar than in CSG 8962. Sand matrix priming (SMP) of seeds using SA @ 150 ppm improved the germination (up to 2 times) and other seed quality parameters in sensitive cultivar under higher (150 mM NaCl) salt-stress level. Further investigating the role of SA on modulating AOE, a negative influence of SA on major AOE (POX, CAT and GR) was observed in cotyledons of PG 186 genotype under high salt stress. However, the level of APX was observed to be constitutively higher in tolerant CSG 8962 chickpea genotype. The summary of results suggested that, SA alleviates oxidative stress through reducing major AOE in cotyledon to improve chickpea seed germination.